2013
DOI: 10.1007/jhep01(2013)009
|View full text |Cite
|
Sign up to set email alerts
|

Amplitudes of 3d Yang Mills theory

Abstract: This paper studies various properties of amplitudes in 3d super Yang Mills theory. First we explain how to obtain the amplitudes of 3d super Yang Mills theories from 4d super Yang Mills theories and obtain their helicity structure. Next, we use a 3d BFCW recursion relation to show that the tree amplitudes and loop integrands of maximal 3d super Yang Mills have dual conformal covariance (although not invariance, so that the amplitudes themselves are not dual conformal). Finally, we argue that the one-loop ampli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 138 publications
1
36
0
Order By: Relevance
“…For this we constructed all standard and hidden symmetries of the massless sixdimensional superamplitudes of N = (1, 1) SYM theory thereby correcting small mistakes in the proof of the dual conformal symmetry given in [4]. We exploited the symmetries of the six-dimensional amplitudes to derive the symmetries of massive tree amplitudes in N = 4 SYM theory and showed that the five dimensional dual conformal symmetry of the massive amplitudes leads to the presence of non-local Yangian-like generators m (1) , p (1) associated to the masses and momenta in on-shell superspace. An interesting open question is whether or not there exist level-one supermomenta as well.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For this we constructed all standard and hidden symmetries of the massless sixdimensional superamplitudes of N = (1, 1) SYM theory thereby correcting small mistakes in the proof of the dual conformal symmetry given in [4]. We exploited the symmetries of the six-dimensional amplitudes to derive the symmetries of massive tree amplitudes in N = 4 SYM theory and showed that the five dimensional dual conformal symmetry of the massive amplitudes leads to the presence of non-local Yangian-like generators m (1) , p (1) associated to the masses and momenta in on-shell superspace. An interesting open question is whether or not there exist level-one supermomenta as well.…”
Section: Discussionmentioning
confidence: 99%
“…αα generator, We note that m (1) can also be obtained from the action of K 5 on the on-shell variables (5.48) in the same way as p (1) has been obtained from K αα in (5.42).…”
Section: Jhep01(2015)098mentioning
confidence: 99%
See 3 more Smart Citations